2005
DOI: 10.1103/physrevb.71.195413
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and Fermi surface of Bi(100)

Abstract: The surface electronic structure of Bi͑100͒ was studied by angle-resolved photoemission and the fullpotential linearized-augmented plane-wave film method. Experimentally, several electronic surface states were identified in the gaps of the projected-bulk band structure close to the Fermi level. Theory shows that these states belong to a spin-orbit split-surface band that extends through the whole Brillouin zone, and that some surface states penetrate very deeply into the bulk. In the experiment, the surface Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Such measurements could establish that the surface Fermi arc encloses an odd number of time-reversal invariant momenta in the strong topological insulator phase. Detailed angle-resolved photoemission spectroscopy studies have been carried out on the surfaces of bismuth [67][68][69] and antimony. 70 However, the presence of the bulk Fermi surface complicates the analysis of these materials.…”
Section: Other Materialsmentioning
confidence: 99%
“…Such measurements could establish that the surface Fermi arc encloses an odd number of time-reversal invariant momenta in the strong topological insulator phase. Detailed angle-resolved photoemission spectroscopy studies have been carried out on the surfaces of bismuth [67][68][69] and antimony. 70 However, the presence of the bulk Fermi surface complicates the analysis of these materials.…”
Section: Other Materialsmentioning
confidence: 99%
“…These two interfaces set up the boundary condition for the quantum states and they can also support localized electronic states at the Fermi level, which could dominate the transport properties of a sufficiently thin film. 5,6,8 Later, it was indeed found that many low-index surfaces of Bi studied are good two dimensional metals [11][12][13][14] ͑for a review see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore performed our measurements on the ͑111͒ surface of Bi for which the electronic structure and even the lifetime of the surface states are well known. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] growth direction for thin films. Our findings have direct relevance for the study of the semimetal to semiconductor transitions in these films.…”
Section: Introductionmentioning
confidence: 99%
“…However, if bulk bismuth is described as topologically trivial [22][23][24] then an unpaired Fermi level crossing is not expected here.…”
mentioning
confidence: 99%